Pertanggungjawaban Pejabat Pembuat Akta Tanah Dalam Dugaan Perbuatan Melawan Hukum Terkait Pengurusan Balik Nama Sertifikat (Studi Putusan Putusan Mahkamah Agung Nomor 175 K/Pdt/2021) - Rahma, Safira Ainur (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
Notaries/PPAT play an important role in ensuring legal certainty in land rights transfers through the creation of authentic deeds and certificate transfer procedures. However, their position is often questioned when obstacles arise in the land administration process. This study examines the responsibility of Notaries/PPATs in the case of Supreme Court Decision No. 175 K/Pdt/2021, in which the PPAT was accused of committing an unlawful act. Using normative juridical and qualitative analysis methods, the study found that the responsibility of Notaries/PPATs is limited to the authority to draw up deeds and submit files to the National Land Agency (BPN). Obstacles in the form of certificate blocking do not constitute negligence on the part of the PPAT. The results of the study emphasize the need for legal protection for Notaries/PPATs so that they can carry out their duties professionally while still providing legal certainty for the community.